Neuromuscular Complications of SARS-CoV-2 and Other Viral Infections - Jacob, Sarah; Kapadia, Ronak; Soule, Tyler; Luo, Honglin; Schellenberg, Kerri L.; Douville, Renée N.; Pfeffer, Gerald (Frontiers in Neurology, 2022)
In this article we review complications to the peripheral nervous system that occur as a consequence of viral infec-tions, with a special focus on complications of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). We discuss neuromuscular complications in three broad categories; the direct consequences of viral infection, auto-immune neuromuscular disorders provoked by viral infections, and chronic neurodegenerative conditions which have been associated with viral infections. We also include discussion of neuromuscular disorders that are treated by immunomodulatory therapies, and how this affects patient susceptibility in the current context of the coronavirus disease 2019 (COVID-19) pandemic. COVID-19 is associated with direct consequences to the peripheral nervous system via presumed direct viral injury (dysgeusia/anosmia, myalgias/rhabdomyolysis, and potentially mo-noneuritis multiplex) and autoimmunity (Guillain Barré syndrome and variants). It has important implications for people receiving immunomodulatory therapies who may be at greater risk of severe outcomes from COVID-19. Thus far, chronic post-COVID syndromes (a.k.a: long COVID) also include possible involvement of the neuromuscular system. Whether we may observe neuromuscular degenerative conditions in the longer term will be an important question to monitor in future studies.